2017
DOI: 10.5114/bta.2017.68313
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of novel and renewable agro-industry by-products into a biodegradable poly(3-hydroxybutyrate) by marine Bacillus megaterium UMTKB-1 strain

Abstract: Agro-industry by-products are abundant in various valuable compounds. Some of these raw materials are considered as a cheaper carbon source for polyhydroxyalkanoate (PHA) production when compared with pure substrates. It is however often a costly affair for industries to recover the residual carbon components. In this study, poly(3-hydroxybutyrate) [P(3HB)] was produced using a marine Bacillus megaterium UMTKB-1 strain from sweetwater, a by-product from cane sugar refining process. The bioconversion was initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…PHA has been commonly generated from municipal wastewater, solid waste, and cheese whey [52,66], waste cooking oil [57,[67][68][69], cane molasses [70], spent coffee grounds [71], phenol [72], food waste [73], sweetwater, a by-product of processing sugar cane [74], nonfood crops such as ryegrass [75], and agro-industrial waste [59]. Although various wastes have been reported to be recoverable to PHA, agricultural crop residues are the most available and investigated carbon substrate that helps in the growth of bacteria culture and PHA production [73]. The main focus that Pakalapati et al showed was on transforming rural, food-derived waste and industrial into PHA [15].…”
Section: Waste Feedstocksmentioning
confidence: 99%
“…PHA has been commonly generated from municipal wastewater, solid waste, and cheese whey [52,66], waste cooking oil [57,[67][68][69], cane molasses [70], spent coffee grounds [71], phenol [72], food waste [73], sweetwater, a by-product of processing sugar cane [74], nonfood crops such as ryegrass [75], and agro-industrial waste [59]. Although various wastes have been reported to be recoverable to PHA, agricultural crop residues are the most available and investigated carbon substrate that helps in the growth of bacteria culture and PHA production [73]. The main focus that Pakalapati et al showed was on transforming rural, food-derived waste and industrial into PHA [15].…”
Section: Waste Feedstocksmentioning
confidence: 99%
“…On the other hand, commercial PHA production is mainly focused on the use of Gram-negative bacteria (e.g., Cupriavidus, Pseudomonas, and E. coli) [9]. Nonetheless, these bacteria have endotoxins (lipopolysaccharides, LPS), which are released in the biopolymer extraction processes and affect their subsequent application in some areas of the industry (e.g., medical and pharmaceutical), thus requiring additional stages of purification [10].…”
Section: Introductionmentioning
confidence: 99%
“…The strains used in this experiment were Massilia haematophila UMTKB-2, isolated from brackish water in Mengabang Telipot, Kuala Terengganu, Terengganu, Malaysia [5] and Bacillus megaterium UMTKB-1, isolated from the tissue sample of marine sponges collected from Pulau Langkawi, Kedah, Malaysia [6] . Bacillus megaterium UMTKB-1 was employed to synthesize homopolymer P(3HB), while Massilia haematophila UMTKB-2 was employed to synthesize copolymer P(3HB- co -3HV).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Bacillus megaterium UMTKB-1 and Massilia haematophila UMTKB-2 were first cultured into a sterile NR medium using shaken flask cultivation method for 14 and 12 h respectively to activate the cells at 200 rotations per minute (rpm) until the mid-exponential growth phase, after which the growth phase was determined by measuring the optical density of the bacterial culture at 600 nm. The biosynthesis, harvesting and recovery of P(3HB) was carried out according to Yatim and co-workers using sweet water [6] , whereas the biosynthesis, harvesting and recovery of P(3HB- co -3HV) was performed according to Kiun and co-workers [5] . Inactivation and removal of endotoxins from the polymers were performed using hydrogen peroxide, after which the endotoxin levels were tested using E-TOXATE™ Kits (Sigma Aldrich) [7] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%